Evaluasi Kesesuaian Aspek Teknis Operasional Sistem Pengelolaan Sampah di Pusat Edukasi Pemanfaatan dan Pengelolaan Sampah Jelekong - Dewi, Arynda; Nico Halomoan (Jurnal Serambi Engineering, 2026)
Population growth and urbanization in Bandung Regency have led to a significant increase in waste generation, necessitating effective and sustainable management efforts. The Jelekong Waste Management and Utilization Education Center (PUSPA) was established as an educational facility based on the Reuse, Reduce, Recycle (3R) principles. This study aims to evaluate the suitability of the technical aspects of the waste management system at PUSPA Jelekong. The study was conducted at PUSPA Jelekong. A quantitative descriptive analysis method was applied based on the 2021 TPS 3R Technical Instructions, resulting in a description of the TPS 3R, the percentage of processed waste, and the percentage of residue. The suitability status of the waste management system at PUSPA is good with a total actual score of 15. The percentage of processed waste is 77.81%, and the percentage of residue is 22.18%. Optimization of TPS 3R can be achieved through efforts to socialize waste management to the community in collaboration with stakeholders, and improving the competence of TPS 3R officers to improve TPS 3R performance.